Sound absorption performance of a filled honeycomb composite structure. (May 2020) - Xie, Suchao; Yang, Shichen; Yang, Chengxing; Wang, Da
Highlights: FHCS structure is lighter than traditional devices and has better effects. Smaller specifications of honeycombs will consume more extra sound waves. The density and thickness of the filling can make the SAC significantly increase. The SAC of the experimental specimen will become stable at high frequencies. Abstract: A new composite structure was formed by filling Nomex honeycomb with polyester fibre to achieve the goal of improving its acoustic characteristics. By using the impedance tube method, the sound absorption coefficient (SAC) of porous materials was determined. Moreover, the effects of different specifications of honeycomb, porosities of fibre, and amount of filler on SAC were studied to achieve the experimental objective. The experimental results demonstrate that the increase of porosity of filler can improve the SAC of the test sample. Honeycombs with different specifications slightly influence the SAC of the sample and the influencing factor may be additional absorption of sound waves caused by contact between materials. Different filling amounts can change the SAC of the sample, while SAC does not improve significantly in the high-frequency range. Simulation results using Virtual Lab. show that porosity of the materials affects the sound absorption performance thereof. The data and conclusions obtained in experiments and simulation provide support for the application of honeycomb sandwich panels in acoustics and noise reduction.